2007
DOI: 10.1088/1367-2630/9/6/184
|View full text |Cite
|
Sign up to set email alerts
|

Robustness of cooperation in the evolutionary prisoner's dilemma on complex networks

Abstract: Recent studies on the evolutionary dynamics of the Prisoner's Dilemma game in scale-free networks have demonstrated that the heterogeneity of the network interconnections enhances the evolutionary success of cooperation. In this paper we address the issue of how the characterization of the asymptotic states of the evolutionary dynamics depends on the initial concentration of cooperators. We find that the measure and the connectedness properties of the set of nodes where cooperation reaches fixation is largely … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
119
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 161 publications
(121 citation statements)
references
References 61 publications
2
119
0
Order By: Relevance
“…On the other hand, the structure of interactions among individuals in real societies are seen to be described by complex networks of contacts rather than by a set of agents connected all-to-all [9,10]. Therefore, it is necessary to abandon the panmixia hypothesis to study how cooperative behavior appear in the social context.Several studies [11,12,13,14,15,16,17,18,19] have reported the asymptotic survival of cooperation on different kinds of networks. Notably, cooperation even dominates over defection in non-homogeneous, scale-free (SF) networks, i.e.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, the structure of interactions among individuals in real societies are seen to be described by complex networks of contacts rather than by a set of agents connected all-to-all [9,10]. Therefore, it is necessary to abandon the panmixia hypothesis to study how cooperative behavior appear in the social context.Several studies [11,12,13,14,15,16,17,18,19] have reported the asymptotic survival of cooperation on different kinds of networks. Notably, cooperation even dominates over defection in non-homogeneous, scale-free (SF) networks, i.e.…”
mentioning
confidence: 99%
“…Several studies [11,12,13,14,15,16,17,18,19] have reported the asymptotic survival of cooperation on different kinds of networks. Notably, cooperation even dominates over defection in non-homogeneous, scale-free (SF) networks, i.e.…”
mentioning
confidence: 99%
“…Rather, they have a degree distribution with a heavy tail, where many nodes have low degrees, but very few nodes have a very high degree each. In the field of evolutionary game theory inhomogenous graphs have been successfully used to study the evolution of cooperation [4,17,[47][48][49][50], but the impact of changing the updating rule on these results is not fully clear.…”
Section: Discussionmentioning
confidence: 99%
“…The link dynamics updating rule (LD) [17] arose from the study of structured populations and focuses on pairwise interactions. In most cases, a population structure is given in terms of a (static) graph [18], in which nodes correspond to individuals in the population.…”
Section: Introductionmentioning
confidence: 99%
“…In this section, we address the opposite case of highly heterogeneous networks, taking scale-free networks (Albert & Barabási, 2002) as our working example. Recent work has pointed out that these networks can be favorable to cooperation (Santos, Pacheco, & Lenaerts, 2006;Poncela, Gó mez-Gardeñ nes, Floría, & Moreno, 2007) and can even self-organize if they grow by incorporating new individuals who choose their neighbors depending on the payoffs of a game (Poncela, Gó mez-Gardeñ nes, Floría, Sán-chez, & Moreno, 2008). Therefore, analyzing the micro-macro link on degree heterogeneous networks is an important subject that deserves attention both on its own and for its possible applications.…”
Section: Degree-heterogeneous Populationsmentioning
confidence: 99%